Maintenance Sistem Pendingin Motor Jupiter MX 135 CC - Maurits Dae; Stefanus Neno (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
The cooling system on the Jupiter MX 135 CC motorcycle functions to maintain a stable engine temperature to prevent overheating. There are two main types of cooling systems on motorcycles: Air Cooling System and Liquid Cooling System. In the Air Cooling System, the working principle involves heat generated by the motorcycle engine being dissipated through cooling fins located around the engine block. Air that flows through the fan or moves as the motorcycle runs will carry away the heat. Meanwhile, in the Liquid Cooling System, the working principle involves coolant (usually a mixture of water and antifreeze) flowing through channels inside the engine to absorb heat. The coolant is then carried to the radiator, where the heat is transferred to the air with the help of a fan. Common problems that occur in the cooling system of the Jupiter MX 135 CC motorcycle can interfere with engine performance and risk causing serious damage if not addressed promptly. Some of the common issues include, Low coolant level, Radiator damage, Water pump failure, Malfunctioning thermostat (thermostat stuck), Leaking or broken radiator hose, Radiator fan malfunction, Dirty or contaminated coolant, Ineffective fan (for air-cooled engines), Overheating due to excessive load. The objectives of this study are to understand how the cooling system on the Jupiter MX 135 CC motorcycle works, to identify damages occurring in the cooling system, and to solve the issue of water pump leakage in the cooling system. The methods used in this research include observation, literature study, interviews, and action methods. The results of problem identification in the cooling system of the Jupiter MX 135 CC motorcycle show, The water jacket gasket is corroded ,The bearing on the water pump is damaged, The water pump impeller is worn out, The radiator pump seal has hardened, causing a squeaking sound around the water pump, Solutions to the problems in the cooling system components include replacing the damaged and worn parts (head gasket, bearing, seal, and impeller) and refilling with new coolant.